Federal research, development, and demonstration priorities for carbon dioxide removal in the United States. (17th January 2018) - Sanchez, Daniel L; Amador, Giana; Funk, Jason; Mach, Katharine J
Abstract: Atmospheric carbon dioxide removal (CDR) technologies may be critical to achieving deep decarbonization. Yet a lack of technical and commercial maturity of CDR technologies hinders potential deployment. Needs for commercialization span research, development, and demonstration (RD&D) activities, including development of new materials, reactors, and processes, and rigorous monitoring of a portfolio of demonstration projects. As a world leader in supporting science and engineering, the United States (US) can play an important role in reducing costs and clarifying the sustainable scale of CDR. To date, federal agencies have focused on voluntary or piecemeal CDR programs. Here, we present a synthesis of research and developement needs, relevant agency authority, barriers to coordination, and interventions to enhance RD&D across the federal government of the US. On the basis of agency authority and expertise, the Department of Energy, Department of Agriculture, Department of the Interior, National Oceanic and Atmospheric Administration, and National Science Foundation are most central to conducting research, funding projects, monitoring effects, and promulgating regulations. Key enablers for successful programs include embracing technological diversity and administrative efficiency, fostering agency buy-in, and achieving commercial deployment. Based on these criteria, the executive branch could effectively coordinate RD&D strategy through two complementary pathways: (1) renewing intra-agency commitment to CDR in five primary agencies, including both research and demonstration, and (2) coordinating research prioritization and outcomes across agencies, led by the Office of Science and Technology Policy and loosely based on the National Nanotechnology Initiative. Both pathways can be stimulated by executive order or Congressional mandate. Executive branch implementation can begin at any time; future Farm and Energy Bills provide legislative vehicles for enhancing programs.